2008
DOI: 10.1159/000118659
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactam Activity against Penicillin-Resistant <i>Streptococcus pneumoniae</i> Strains Exhibiting Higher Amoxicillin versus Penicillin Minimum Inhibitory Concentration Values: An in vitro Pharmacodynamic Simulation

Abstract: Background: Activity of simulated serum concentrations after oral therapy with 400 mg cefditoren pivoxil b.i.d., 500 mg cefuroxime axetil b.i.d. and 875/125 mg amoxicillin/clavulanic acid b.i.d. and t.i.d. regimens was explored over 24 h against Streptococcus pneumoniae.Methods: Computerized pharmacodynamic simulations were performed against strains with penicillin/amoxicillin/cefuroxime/cefditoren minimum inhibitory concentrations (MICs, µg/ml) and serotypes: strain 1 (0.25/0.12/1/0.12; serotype 6A), strain 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…According to pharmacokinetic-pharmacodynamic principles, the appropriate dose of amoxicillin is the one that maximizes the time when the plasma concentration persists above the MICs of the etiological agent (t > MIC) [43]. For that reason, the aim is to increase the t > MIC by increasing the number of daily doses to achieve bactericidal activity against isolates with MIC ≥ 2 mg/l [18,20,44]. To assure the therapeutic effect for at least 95% of pneumococcal infections in the context, the recommended dose of amoxicillin at 25 mg/kg × 3 times daily thus appears to be too low [32,42,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to pharmacokinetic-pharmacodynamic principles, the appropriate dose of amoxicillin is the one that maximizes the time when the plasma concentration persists above the MICs of the etiological agent (t > MIC) [43]. For that reason, the aim is to increase the t > MIC by increasing the number of daily doses to achieve bactericidal activity against isolates with MIC ≥ 2 mg/l [18,20,44]. To assure the therapeutic effect for at least 95% of pneumococcal infections in the context, the recommended dose of amoxicillin at 25 mg/kg × 3 times daily thus appears to be too low [32,42,44].…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, the aim is to increase the t > MIC by increasing the number of daily doses to achieve bactericidal activity against isolates with MIC ≥ 2 mg/l [18,20,44]. To assure the therapeutic effect for at least 95% of pneumococcal infections in the context, the recommended dose of amoxicillin at 25 mg/kg × 3 times daily thus appears to be too low [32,42,44]. The guidance to increase the dose needs to be further demonstrated by clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in our microbiologic results, no isolates had an MIC of greater than 2 g/ml. Sevillano et al [26] , using a pharmacodynamic simulation model, demonstrated bactericidal activity of oral cefuroxime for strains of S. pneumoniae with MIC of 2 g/ml. Mandell et al [27] , in revised guidelines for management of community-acquired pneumonia, lists cefuroxime as acceptable treatment for S. pneumoniae not resistant to penicillin (MIC !…”
Section: Discussionmentioning
confidence: 99%
“…29 For that reason, the aim is to increase the t > MIC condition by increasing the number of daily doses in order to achieve bactericidal activity against isolates with an MIC of >2 mg/L. 14,15,30 To assure that the therapeutic effect is achieved for at least 88% of pneumococcal infections in this context, the…”
Section: Breakpoints Eucast S (N) S (%) I (N) I (%) R (N) R (%)mentioning
confidence: 99%